Effect on Insulin upon Storage in Extreme Climatic Conditions (Temperature and Pressure) and Their Preventive Measures - Khurana, Girish; Gupta, Vipul (Journal of Social Health and Diabetes, 2019)
Insulin is a naturally occurring hormone secreted by the pancreas. Insulin is required by the body cellsto remove and use glucose from the blood. The insulin and its various analogues are essential in management of type 1 diabetes mellitus. This study has been done to analyze how variation in various storage conditions and climatic changes causes change in therapeutic efficacy. Storage condition affects the stability of insulin as observed in a study in which insulin stored at temperature between 32 and 37°C showed 14 to 18% decrease in its potency and could not cause a significant decrease in blood sugar level when compared with those receiving insulin stored at 5°C. This work was done with the aim of finding the effect of climatic changes and storage condition on efficacy of insulin.
Keywords: insulin; climatic changes; therapeutic efficacy